Preparation method of polyaniline-doped chromium adsorption biomass hydrogel material

By using hydrogel materials prepared by polyvinyl alcohol, chitosan, sodium lignin sulfonate and polyaniline, the problems of high cost and secondary pollution of heavy metal ion adsorption materials in the prior art are solved, and efficient and environmentally friendly Chromium ion removal effect.

CN119186520APending Publication Date: 2024-12-27TIANJIN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411408310.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing heavy metal ion adsorbent materials are costly and prone to secondary pollution. Especially when dealing with chromium-containing wastewater, the selection and regeneration of adsorbents are still technical challenges.

Method used

Polyvinyl alcohol, chitosan, sodium lignin sulfonate and polyaniline were used as raw materials to prepare chromium adsorption biomass hydrogel materials doped with polyaniline through freeze-thaw cycle method, and use hydrogels as carriers for polyaniline particles. , improves the removal capacity of Cr(VI) and avoids secondary pollution.

Benefits of technology

It achieves a low-cost and environmentally friendly heavy metal ion adsorption effect, improves the removal ability of Cr(VI), and maintains a high-efficiency removal rate in multiple cycles, avoiding secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186520A_ABST
    Figure CN119186520A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyaniline-doped chromium adsorption biomass hydrogel material, and belongs to the field of functional materials. The preparation method of the hydrogel comprises the following steps: (1) preparing a polyvinyl alcohol solution, a chitosan solution and a sodium lignin sulfonate solution, and (2) mixing and stirring the polyvinyl alcohol solution, the chitosan solution and the sodium lignin sulfonate solution according to a certain proportion to obtain a polyvinyl alcohol-chitosan-sodium lignin sulfonate mixed solution; and (3) adding the polyaniline particles into the polyvinyl alcohol-chitosan-sodium lignin sulfonate mixed solution, and uniformly stirring. And 4) performing multiple freezing and thawing cycles on the obtained polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline mixed solution, and performing physical crosslinking to prepare the hydrogel. According to the preparation method of the hydrogel, the industrial waste lignin is fully utilized, a new way is provided for high-value utilization of the lignin, and meanwhile, the prepared hydrogel has good adsorption capacity on heavy metal chromium ions and also has good durability and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, and in particular relates to a method for preparing a polyaniline-doped chromium-adsorbed biomass hydrogel material. Background Art

[0002] Heavy metal pollution refers to the phenomenon that certain heavy metal elements, such as lead, cadmium, mercury, chromium, arsenic, etc., enter the environment (mainly soil, water and atmosphere) under the influence of human activities, and cause harm to the ecosystem and human health due to their toxicity and bioaccumulation. These heavy metal elements exist in low concentrations in nature, but are released into the environment through industrial, agricultural and daily life activities, causing their concentrations to exceed the natural background value and ecological safety threshold.

[0003] Chromium pollution mainly comes from industrial activities, especially wastewater discharge from metal processing, electroplating, leather making and other industries. Chromium exists in the environment in trivalent (Cr(III)) and hexavalent (Cr(VI)) forms. The toxicity of hexavalent chromium is much higher than that of trivalent chromium, posing a serious threat to human health and the ecological environment. The impact of chromium pollution on the environment includes inhibiting the nitrification of organic matter in the soil, causing chromium to accumulate in plants, and having a lethal effect on aquatic organisms. Hexavalent chromium is also a strong mutagenic substance. Long-term or short-term exposure to hexavalent chromium ions can induce lung cancer, nasopharyngeal cancer, skin damage, and respiratory and gastrointestinal diseases. Although trivalent chromium is less toxic, large amounts of ingestion can still cause harm to the human body, such as gastrointestinal irritation and gastric ulcers. Therefore, the prevention and control of heavy metal pollution, especially chromium ions, is of great significance.

[0004] The methods for treating chromium-containing wastewater mainly include chemical precipitation, ion exchange, membrane filtration and adsorption. Although the chemical precipitation method has a low cost, it is prone to secondary pollution. Although the ion exchange method and membrane filtration method can effectively remove Cr(VI), the operating cost is high and the membrane material is easily contaminated. The adsorption method is considered to be an economical and effective treatment method, but the selection and regeneration of its adsorbents remain technical challenges. Hydrogel, as a three-dimensional network structure material with high water absorption and good biocompatibility, has shown great application potential in the field of adsorption in recent years. The high porosity and adjustable chemical functionality of hydrogel make it an ideal adsorption material, especially in the removal of heavy metal ions from water.

[0005] Chitosan is a natural polymer material with rich amino and hydroxyl functional groups. It has been widely studied for its excellent biocompatibility, biodegradability and adsorption capacity for a variety of heavy metal ions. Chitosan can effectively adsorb chromium ions in solution. The amino and hydroxyl groups of chitosan can form stable complexes with chromium ions, thereby reducing their concentration in the environment. However, pure chitosan has weak acid resistance and poor adsorption effect in low pH environments. Therefore, in order to improve the acid resistance of chitosan hydrogel and expand its application range, polyvinyl alcohol can be introduced to enhance the acid resistance and mechanical strength of the hydrogel.

[0006] Lignin sulfonate, as a derivative of lignin, has rich active functional groups, excellent elasticity, hydrophobicity and good surface activity, which make it show wide application potential in many fields. However, in the papermaking industry, lignin is produced in large quantities as a by-product, but its application range is limited, resulting in a large amount of lignin resources not being fully utilized.

[0007] Polyaniline is a conductive polymer that shows good application prospects in the field of wastewater treatment due to its unique redox properties, proton doping ability, adjustable conductivity, and strong chemical and environmental stability. In the treatment of chromium-containing wastewater, the adsorption performance of polyaniline and its composite materials has attracted particular attention. The amino groups in the polyaniline molecular chain can form stable complexes with chromium ions, especially hexavalent chromium (Cr(VI)) and trivalent chromium (Cr(III)). The redox properties of polyaniline enable it to reduce Cr(VI) to Cr(III) through reduction reactions, reducing toxicity. However, polyaniline particles are prone to agglomeration and leakage in aqueous solution environments, which reduces the adsorption effect and causes secondary pollution to the environment.

[0008] Therefore, by utilizing the reducing property of polyaniline and loading it in hydrogel, the adsorption of chromium-containing heavy metal waste liquid can be achieved, and the polluted water environment can be repaired. Among them, polyaniline (PANI) can reduce Cr(VI) to Cr(III), reducing the toxicity of chromium ions. Polyvinyl alcohol (PVA), chitosan (CS), and sodium lignin sulfonate (LS) are selected as hydrogel materials, which are environmentally friendly. Hydrogel, as a carrier of polyaniline particles, effectively reduces the secondary pollution of the adsorbent to the environment. Summary of the invention

[0009] The present invention provides a novel hydrogel adsorption material in view of the shortcomings of existing heavy metal ion adsorption materials such as high cost and easy secondary pollution during preparation and application.

[0010] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0011] A method for preparing a chromium-adsorbed biomass hydrogel material doped with polyaniline, wherein the preparation of the hydrogel comprises the following steps:

[0012] Step 1: prepare polyvinyl alcohol, chitosan and sodium lignin sulfonate solutions, and prepare three solutions with different mass concentrations respectively.

[0013] Step 2: prepare a polyvinyl alcohol-chitosan-sodium lignin sulfonate mixed solution, mix the prepared polyvinyl alcohol, chitosan and sodium lignin sulfonate solution in a certain ratio and stir them thoroughly.

[0014] Step 3: prepare a polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline mixed solution, add polyaniline particles into the polyvinyl alcohol-chitosan-sodium lignin sulfonate mixed solution and stir thoroughly.

[0015] Step 4: preparing polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline hydrogel, subjecting the uniformly stirred polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline mixed solution to freeze-thaw cycles to prepare a polyaniline-doped chromium-adsorbing biomass hydrogel.

[0016] Furthermore, the preparation of polyvinyl alcohol, chitosan and sodium lignin sulfonate solution in step 1 includes the following steps: preparing polyvinyl alcohol solution: adding polyvinyl alcohol (analytical pure) particles to deionized water, heating and stirring in a water bath until uniform and transparent, the heating temperature is 70-90°C, the stirring time is 6-12h, and the mass concentration of the prepared polyvinyl alcohol solution is 1-30%; preparing chitosan solution: adding chitosan (analytical pure) powder to dilute acetic acid solution, heating and stirring in a water bath until uniform and transparent, the heating temperature is 40-60°C, the mass concentration of the dilute acetic acid solution is 2-4%, the stirring time is 6-12h, and the mass concentration of the prepared chitosan solution is 0.5-10%; preparing sodium lignin sulfonate solution: adding sodium lignin sulfonate (analytical pure) powder to deionized water, heating and stirring in a water bath until uniform, the heating temperature is 20-40°C, the stirring time is 6-12h, and the mass concentration of the prepared sodium lignin sulfonate solution is 1-20%.

[0017] Furthermore, in step 2, a polyvinyl alcohol-chitosan-sodium lignin sulfonate mixed solution is prepared: polyvinyl alcohol and chitosan solution are mixed in a mass ratio of 4:1 to 1:4, and then the sodium lignin sulfonate solution is added, and stirred in a water bath until the solution is uniform, wherein the amount of sodium lignin sulfonate solution added is 2 to 10 g; the stirring time of the mixed solution is 6 to 12 hours.

[0018] Furthermore, in step 3, a polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline mixed solution is prepared, and polyaniline particles are added to the uniform polyvinyl alcohol-chitosan-sodium lignin sulfonate mixed solution, and stirred in a water bath until the solution is uniform, wherein the amount of polyaniline added is 0.5 to 2 g; and the stirring time of the mixed solution is 6 to 12 hours.

[0019] Furthermore, the polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline hydrogel is prepared as described in step 4, and the polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline mixed solution in step 3 is poured into a mold, the mold is placed in a low-temperature freezer, and then thawed at room temperature, and the freeze-thaw cycle is repeated to prepare the hydrogel.

[0020] Furthermore, in the freeze-thaw cycle described in step 4, the freezing temperature is -20 to -50°C; the freezing time is 12 to 24 hours; the melting temperature is 20 to 40°C; and the number of freeze-thaw cycles is 2 to 5 times.

[0021] The advantages of the present invention are:

[0022] Chitosan, polyvinyl alcohol and sodium lignin sulfonate are used as raw materials, which have wide sources and low costs, and at the same time open up a new way for the high-value utilization of lignin materials.

[0023] The freeze-thaw method is used to prepare the hydrogel, which has a simple operation process and is environmentally friendly.

[0024] Using hydrogel as a carrier of polyaniline particles improves the removal capacity of Cr(VI) while avoiding secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 The effect of different mass ratios of PVA and CS in comparative example 1 on the adsorption of Cr(VI) ions in PVA / CS hydrogels;

[0027] Figure 2 The effect of different addition amounts of LS on the adsorption of Cr(VI) ions in PVA / CS / LS hydrogel prepared in Comparative Example 2 under the optimal parameter conditions of Comparative Example 1;

[0028] Figure 3 The effect of different addition amounts of PANI on the adsorption of Cr(VI) ions in PVA / CS / LS / PANI hydrogel prepared in Comparative Example 3 under the optimal parameter conditions of Comparative Example 2;

[0029] Figure 4 This is a picture of the adsorption cycle performance of the PVA / CS / LS / PANI hydrogel in Example 1;

[0030] Figure 5 , Figure 6 This is the SEM image of comparative example 1 before and after adsorption. Figure 7 , Figure 8 This is the SEM picture of comparative example 2 before and after adsorption. Fig. 9 , Fig.10 This is the SEM image of comparative example 3 before and after adsorption. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the technical scheme of the present invention is further described below in conjunction with the accompanying drawings, embodiments and comparative examples. However, the present invention is not limited to the embodiments listed, and should also include any other known changes within the scope of the rights claimed by the present invention.

[0032] First, the "embodiment 1" referred to herein refers to specific features, structures and characteristics that may be included in at least one implementation of the present invention. Second, when describing the embodiments of the present invention in detail, for ease of explanation, the schematic diagrams will not be partially enlarged to a general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional space of length, width and depth should be included.

[0033] In addition, the abbreviations mentioned in the present invention are all fixed abbreviations in the art, and some of the letters are explained as follows: PVA: polyvinyl alcohol; CS: chitosan; LS: sodium lignin sulfonate; PANI: polyaniline; SEM: scanning electron microscope.

[0034] Comparative Example 1

[0035] This comparative example prepared a PVA / CS chromium adsorption hydrogel material according to the following steps

[0036] Step 1: Preparation of PVA / CS hydrogel

[0037] PVA (mass concentration 12%) solution and CS (mass concentration 4%) solution were mixed in a mass ratio of 2:1; 1:1; 1:2, respectively, stirred in a water bath at 30°C for 6 hours until the mixture was uniform, and then subjected to ultrasonic degassing. The uniformly mixed PVA / CS solution was poured into a mold, and the mold was frozen at -20°C for 12 hours, then taken out and thawed at room temperature. Repeat 3 times to obtain PVA / CS hydrogel.

[0038] Step 2: Apply the prepared PVA / CS hydrogel material for adsorption

[0039] 0.1g of PVA / CS hydrogel prepared according to different mass ratios was added to 40mL of Cr(VI) ion solution with pH=2 and initial concentration of 100mg / L. After heating in a water bath at 40℃ for 48h, the supernatant was taken and the residual Cr(VI) ion concentration of the solution was measured at 540nm by UV-visible spectrophotometer after adding the color developer. The experimental results show that the hydrogel prepared according to the mass ratio of 1:1 has the best adsorption capacity, reaching 9.48mg / g.

[0040] Comparative Example 2

[0041] This comparative example prepared a PVA / CS / LS chromium adsorption hydrogel material according to the following steps

[0042] Step 1: Preparation of PVA / CS / LS hydrogel

[0043] Take the most preferred mass ratio of PVA and CS in Comparative Example 1, mix 10g of PVA (mass concentration 12%) solution and 10g of CS (mass concentration 4%) solution, then add 2, 4, and 6g of LS (mass concentration 10%) solution, stir in a water bath at 30°C for 6h until mixed evenly, and then perform ultrasonic degassing. Pour the evenly mixed PVA / CS / LS solution into a mold, freeze the mold at -20°C for 12h, take it out, and thaw it at room temperature. Repeat 3 times to obtain PVA / CS / LS hydrogel.

[0044] Step 2: Apply the prepared PVA / CS / LS hydrogel material for adsorption

[0045] 0.1g of PVA / CS / LS hydrogel with different sodium lignin sulfonate additions was added to 40mL of Cr(VI) ion solution with pH=2 and initial concentration of 100mg / L, and heated in a water bath at 40℃ for 48h. The supernatant was taken, and after adding the color developer, the residual Cr(VI) ion concentration of the solution was measured at 540nm by UV-visible spectrophotometer. The experimental results show that the hydrogel prepared with LS addition of 4g has the best adsorption capacity, reaching 17.33mg / g.

[0046] Comparative Example 3

[0047] This comparative example prepared a PVA / CS / LS / PANI chromium adsorption hydrogel material according to the following steps

[0048] Step 1: Preparation of PVA / CS / LS / PANI hydrogel

[0049] Take the optimal LS addition amount in comparative example 2, mix 10g of PVA (mass concentration 12%) solution, 10g of CS (mass concentration 4%) solution and 4g of LS (mass concentration 10%) solution, stir in a water bath at 30°C for 6h until mixed evenly, add 0.5, 1, and 1.5g of PANI particles, continue to stir in a water bath at 30°C for 12h until mixed evenly, and perform ultrasonic degassing. Pour the evenly mixed PVA / CS / LS / PANI solution into a mold, freeze the mold at -20°C for 12h, take it out, and thaw it at room temperature. Repeat 3 times to obtain PVA / CS / LS / PANI hydrogel.

[0050] Step 2: Apply the prepared PVA / CS / LS / PANI hydrogel material for adsorption application

[0051] 0.1g of PVA / CS / LS / PANI hydrogel with different amounts of polyaniline particles was added to 40mL of Cr(VI) ion solution with pH=2 and initial concentration of 100mg / L, and heated at 40℃ in a water bath for 48h. The supernatant was taken, and after adding the developer, the residual Cr(VI) ion concentration of the solution was measured at 540nm by UV-visible spectrophotometer. The experimental results show that the hydrogel prepared with 1.5g of PANI has the best adsorption capacity, reaching 39.99mg / g.

[0052] Embodiment 1

[0053] This embodiment prepares a method for preparing a chromium-adsorbing biomass hydrogel material (PVA / CS / LS / PANI) doped with polyaniline under the above-mentioned optimal parameters.

[0054] Step 1: Preparation of PVA / CS / LS / PANI hydrogel

[0055] Mix 10g of PVA (mass concentration 12%) solution, 10g of CS (mass concentration 4%) solution and 4g of LS (mass concentration 10%) solution, stir in a water bath at 30°C for 6h until the mixture is uniform, add 1.5g of PANI particles, continue stirring in a water bath at 30°C for 12h until the mixture is uniform, and perform ultrasonic degassing. Pour the uniformly mixed PVA / CS / LS / PANI solution into a mold, freeze the mold at -20°C for 12h, take it out, and thaw it at room temperature. Repeat 3 times to obtain PVA / CS / LS / PANI hydrogel.

[0056] Step 2: Apply the prepared PVA / CS / LS hydrogel material for adsorption

[0057] Take 0.1 g of PVA / CS / LS / PANI hydrogel and add it to 40 mL of Cr(VI) ion solution with an initial concentration of 100 mg / L at pH 2. After heating in a water bath at 40°C for 48 h, take the supernatant, add the color developer, and measure the residual Cr(VI) ion concentration of the solution at 540 nm using a UV-visible spectrophotometer.

[0058] Step 3: Circulate the adsorbed PVA / CS / LS / PANI hydrogel material for adsorption application

[0059] The adsorbed hydrogel was taken out and soaked in 40mL, 0.1mol / LHCl for half an hour under ultrasound to achieve the purpose of desorption, and then repeatedly soaked in deionized water until the pH of the solution reached neutral. The desorbed adsorbent was then added to 40mL, pH=2, Cr(VI) ion solution with an initial concentration of 100mg / L and heated at 40°C in a water bath for 48h. The supernatant was taken, and after adding the color developer, the remaining Cr(VI) ion concentration of the solution was measured at 540nm by a UV-visible spectrophotometer. The cycle experiment was repeated 5 times. The results show that after 5 adsorption cycles, the removal rate of the hydrogel adsorbent remained above 85%.

[0060] In summary, the present invention discloses a method for preparing a chromium-adsorbing biomass hydrogel material doped with polyaniline. The method is more environmentally friendly and has low cost, simple process and easy operation compared with the existing preparation technology, and solves the problems of low utilization rate of lignin and secondary pollution easily caused by adsorbents.

[0061] It should be noted that the above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a chromium-adsorbing biomass hydrogel material doped with polyaniline, characterized in that: The preparation method comprises the following steps: firstly preparing polyvinyl alcohol, chitosan and sodium lignin sulfonate solutions of a certain concentration, then mixing and stirring the three solutions in a certain ratio, then adding a certain amount of polyaniline particles into the polyvinyl alcohol-chitosan-sodium lignin sulfonate mixed solution and stirring the mixture evenly, and finally subjecting the polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline mixed solution to multiple freeze-thaw cycles to obtain a hydrogel material for chromium ion adsorption.

2. The method for preparing a polyaniline-doped chromium-adsorbing biomass hydrogel material according to claim 1, characterized in that: A certain mass of polyvinyl alcohol (analytical grade) particles is added to deionized water, and magnetically stirred in a water bath until uniform to prepare a polyvinyl alcohol solution with a certain mass concentration, wherein the mass concentration of the polyvinyl alcohol solution is 1-30%, the stirring temperature is 70-90° C., and the stirring time is 6-12 h.

3. The method for preparing a chromium-adsorbing biomass hydrogel material doped with polyaniline according to claim 1, characterized in that: A certain mass of chitosan (analytical pure) powder is added to a dilute acetic acid solution, and magnetically stirred in a water bath until uniform to prepare a chitosan solution of a certain mass concentration, wherein the mass concentration of the chitosan solution is 0.5-10%, the mass concentration of the dilute acetic acid solution is 2-4%, the stirring temperature is 40-60°C, and the stirring time is 6-12h.

4. The method for preparing a polyaniline-doped chromium-adsorbing biomass hydrogel material according to claim 1, characterized in that: A certain mass of sodium lignin sulfonate (analytical grade) powder is added to deionized water, and magnetically stirred in a water bath until uniform to prepare a sodium lignin sulfonate solution with a certain mass concentration, wherein the mass concentration of the sodium lignin sulfonate solution is 1-20%, the stirring temperature is 20-40° C., and the stirring time is 6-12 h.

5. The method for preparing a polyaniline-doped chromium-adsorbing biomass hydrogel material according to claim 1, characterized in that: The polyaniline particles are in a conductive state, and the particle diameter is 1 nm to 500 μm.

6. The method for preparing a polyaniline-doped chromium-adsorbing biomass hydrogel material according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol to chitosan solution in the polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline mixed solution is 4:1-1:4; the amount of sodium lignin sulfonate solution added is 2-10g; the amount of polyaniline particles added is 0.5-2g; the stirring time of the polyvinyl alcohol-chitosan-sodium lignin sulfonate mixed solution and the polyvinyl alcohol-chitosan-sodium lignin sulfonate-polyaniline mixed solution is 6-12h.

7. The method for preparing a polyaniline-doped chromium-adsorbing biomass hydrogel material according to claim 1, characterized in that: The freezing temperature in the freeze-thaw cycle is -20 to -50°C; the freezing time is 12 to 24 hours; the melting temperature is 20 to 40°C; and the number of freeze-thaw cycles is 2 to 5 times.

8. The method for preparing a polyaniline-doped chromium-adsorbing biomass hydrogel material according to claims 1 to 7, characterized in that: The hydrogel material can be applied to fields such as industrial wastewater remediation and soil remediation.